Efektivitas Pelaksanaan Hukum Cambuk Bagi Pelaku Zina ddi Nanggroe Aceh Darussalam Perspektif Hukum Pidana Islam - Filla Rusni Madjie,; Laisya Ramadhani,; Deden Najmudin, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The application of flogging for adultery in Nanggroe AcehDarussalam is a form of Islamic law implementation that has a specific legal basisthrough the Qanun Jinayat. However, its effectiveness in the perspective ofIslamic criminal law still raises normative debates. This studyaims to analyze the harmony between the provisions of flogging in the qanunand the principles of Islamic criminal law, as well as to assess its normative effectivenessbased on the objectives of Sharia law. The method used is normative juridical researchwith a legislative and conceptual approach through a reviewof national regulations, qanun, and fiqh jinayah literature.The results show that the provisions on flogging in the Qanun Jinayat are generallyin line with the principles of hudud and the principle of prudence, but there areseveral modifications that affect its normative effectiveness, particularly in relation toevidence and the objective of prevention. The novelty of this research lies in itscomprehensive analysis linking normative effectiveness with maqashidal-syari'ah. Its academic contribution is to provide a normative evaluation framework for assessing the application of Islamic criminal law in the context of a modern state